The collaborative economy and taxation: taxing the value created in the collaborative economy - Remeur, Cécile (Brussels, 2018)
"EU citizens' daily lives have been changed by the emerging collaborative economy. However, the terms employed to describe the phenomenon are as many and varied as the interpretations of what the collaborative economy actually comprises. The collaborative economy encompasses many situations that do not match the standard business categories and types of transactions. The collaborative economy blurs the lines, not least as regards taxation. For policy-makers to understand how taxation of the collaborative economy can be put into practice requires fighting the surrounding fog of terms and categories. Privileging a case-by-base and tax-by-tax, rather than a straightforward 'one-size-fits-all' approach, is a prerequisite for grasping the potential benefits of this fast-evolving and multifaceted reality."